Assessment of evaporative cooling efficiency in greenhouses equiped with wetted porous plates - Flavio Alves-Damasceno; Luciano Barreto-Mendes; Tadayuki Yanagi Junior; Jofran Luiz de Oliveira; Jairo Alexander Osorio-Saraz (Dyna, 2017)
The main objective of this study was to experimentally validate a mechanistic model for predicting the cooling efficiency (η) of wetted porous plates built with expanded clay. The expanded clay material was physically characterized by specific mass, surface area, and volume. The model was validated with dry bulb temperature (Tdb, °C) and air relative humidity (RH, %) data, which were continuously monitored in two different points, upstream and downstream the direction of the air passing through the porous plate. Data collection was carried out consecutively for a period of 10 days, between 11:00 a.m. and 4:00 p.m. Average values for η, simulated and observed, were 74.8 ± 7.4% and 68.3 ± 8.3%, respectively. Based on the developed model, it was observed that η was higher than 40% for Tdb > 30 °C and constant RH at 45%. The simulation for predictions indicates that the increase in the air temperature greater than 20 °C may affect negatively the production in greenhouses from states located in tropical and subtropical countries as Minas Gerais, Brazil, if some design criteria in the evaporative cooling system are not revised.